2009
DOI: 10.1158/0008-5472.can-09-0400
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Administration of Artificial Antigen-Presenting Cells Activates Low-Avidity T Cells for Treatment of Cancer

Abstract: The development of effective antitumor immune responses is normally constrained by low-avidity, tumor-specific CTLs that are unable to eradicate the tumor. Strategies to rescue antitumor activity of low-avidity melanoma-specific CTLs in vivo may improve immunotherapy efficacy. To boost the in vivo effectiveness of low-avidity CTLs, we immunized mice bearing lung melanoma metastases with artificial antigen-presenting cells (aAPC), made by covalently coupling pep MHC-Ig dimers and B7

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…In contrast, significant fractions of IFN-g-competent CD8 þ T CM cells were found in slightly longer ex vivo assays (24 hours). Interestingly, the 24-hour ICP assay also allowed enumeration of intermediate/low avidity TRP-2-specific memory CD8 þ T cells (31). We believe .…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, significant fractions of IFN-g-competent CD8 þ T CM cells were found in slightly longer ex vivo assays (24 hours). Interestingly, the 24-hour ICP assay also allowed enumeration of intermediate/low avidity TRP-2-specific memory CD8 þ T cells (31). We believe .…”
Section: Discussionmentioning
confidence: 88%
“…That said, there may be circumstances wherein lower avidity cells play a critical role. For example, cells exhibiting reduced avidity may be protected from exhaustion in models of chronic antigen exposure (15) and may play important roles in the clearance of some tumor cells (54,57,58).…”
mentioning
confidence: 99%
“…It has also been reported that i.v. injection of Kb-expressing aAPC into C57BL/6 mice resulted in decreased lung metastasis of tumor 21 . Importantly, these data demonstrate that aAPC traffic to the lung and are able to activate effector T cell subsets.…”
Section: Discussionmentioning
confidence: 96%